Jóvenes investigadores en tic: de los temas de estudio a la carrera académica - Sanchéz Gil, Juana Mª (Revista Fuentes, 2013)
Este artículo se basa en el contenido del taller “Jóvenes investigadores en TIC”, del que fui coordinadora por invitación de los organizadores de las XIX Jornadas Universitarias de Tecnología Educativa, que tuvieron lugar en Sevilla, en noviembre de 2011. Tras explicar el sentido de esta actividad, se plantean algunos posicionamientos sobre la noción de Tecnología Educativa, para pasar a presentar, en forma de narración, cómo se articuló la sesión y profundizar en algunas de las cuestiones que se debatieron. Unas temáticas que van desde qué entendemos por investigación a cómo afrontar la carrera académica. Abstract The aim of the paper is to present a variety of case studies on training and research that have occurred in the Open Education Movement, particularly in the Latin American context, together with the development of emerging technologies that have contributed greatly to the movement. The methodology presented is based on a case study research, specifically four cases: (a) researcher training with a research group through the Professorship on Innovation Research in Technology and Education (CIITE), (b) construction of knowledge through projects funded by a Mexican network of educational research with the University Corporation for Internet Development (CUDI), (c) generation of advanced networks with support from the Regional Open Latin American Community for Social and Educational Research (CLARISE) and (d) CLARISE distance education (SINED-CLARISE). The results and achievements were supported by several studies about the open education movement, the production of technological developments as open educational resources (OER), open repository, open repositories metadata harvester and enrichment of OER indexing systems. The challenges and opportunities lie in making this movement public, developing a shared culture, respect for legality and copyrights, developing financial models to make it sustainable, and the need of institutional and national laws that support open educational practices.